Pengaruh Media Playdough Terhadap Perkembangan Kognitif Sains Anak Kelompok B di KB Tunas Bangsa Kecamatan Mumbulsari - Hilmaliana Putri; Ratnasari Dwi Ade Chandra; Hendrik Siswono (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THIS TITLE OF ARTICLES IN ENGLISH VERSION (Title Have To Use Capital Initial Letter, 10 pt Bold Font) Abstract. Abstract: Cognitive development is an important aspect of early childhood education (ECE) that influences children's readiness for the next level of education. However, the cognitive development of children at KB Tunas Bangsa is still considered low due to conventional teaching methods. This study aims to examine the effect of playdough media on the cognitive development of science in Group B children at KB Tunas Bangsa. The method used is quantitative research with a pre-experimental design, specifically the One Group Pretest-Posttest Design. The population of the study includes all students in Group B, with subjects taken purposively totaling 15 children. Data were collected through tests, observations, and documentation focusing on cognitive aspects, including similarities, differences, classification, and cause-and-effect relationships. Data analysis was conducted using normality tests, homogeneity tests, and paired sample t-tests. The results showed an increase in the average pretest score from 64 to 86 in the posttest. The t-test yielded a significance value of 0.000 < 0.05, leading to the rejection of Ho and acceptance of Ha. This indicates that the use of playdough media has a significant effect on the cognitive development of science in Group B children at KB Tunas Bangsa